Reality TV shows and the shifting youth identity in Nigeria: maltina dance all as a case (2015)
This paper examines the shifting identity of youth as reflected in the role they and adults play in Maltina Dance All, a Nigerian reality TV programme. Besides the globalisation thesis, the paper pays attention to the roles the young people and their adult relatives play in Maltina Dunce All reality TV show, bringing out the meanings invoked in parents participation in the programme, and the implications of this on youth identity, and on the Nigeria social space. The study adopts Scheduler's performance theory as a framework to interpret the patterned behaviour of youth and adults in the show. Qualitative methods of in-depth interview, focus group discussion and observation were used for data collection. Informants included 45 undergraduate students of University of Ibadan, Nigeria, who are regular viewers of Maltina Dance All, and 25 adults who are parents. Older adults were interviewed to discover their perception of adults' participation in the programme, and what it portends for youth identity and the socio-cultural change in Nigeria. Analysis of data involved descriptive and interpretive analyses. Participation in reality TV programmes offers the youth the opportunity to create hegemony of power and presence, establish their autonomy and circumvent the control of the adult. Capitalising on the periphery, through centring the youth culture, young people emerge as leaders while parents learn from their children the dance steps and the expectations of the panel of judges. This cultural reversal demonstrates the shifting identity of youth as occasioned by the influence of media-led globalisation and innovations in information technology on Nigeria’s sociocultural development.